2008
DOI: 10.1063/1.2838734
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of GaN (Fe) buffers for AlGaN∕GaN high electron mobility transistor structures

Abstract: The electrical properties of AlGaN∕GaN high electron mobility transistor structures grown on composite GaN(Fe)∕GaN buffers by molecular beam epitaxy were reported. The concentration of Fe in the GaN(Fe) layer ranged from 8×1016to3×1017cm−3 as established by secondary ion mass spectrometry. The thickness of the undoped GaN layer of the buffer was varied from 2.2to4.1μm. For thinner buffers and higher Fe concentration, the buffer was semi-insulating, with the Fermi level pinned near Ec-0.57eV. For thicker buffer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…[181,182] showed that the resistivity of the GaN films consisting of the heavily Fe doped layer near sapphire and an undoped portion of the film higher up increased with increased Fe doping in the Fe-doped subbuffer and with decreased thickness of the undoped portion of the buffer [181]. The semi-insulating samples with combined buffer showed the Fermi level pinned near E c À0.6 eV.…”
Section: Fe Doping Effectsmentioning
confidence: 97%
See 2 more Smart Citations
“…[181,182] showed that the resistivity of the GaN films consisting of the heavily Fe doped layer near sapphire and an undoped portion of the film higher up increased with increased Fe doping in the Fe-doped subbuffer and with decreased thickness of the undoped portion of the buffer [181]. The semi-insulating samples with combined buffer showed the Fermi level pinned near E c À0.6 eV.…”
Section: Fe Doping Effectsmentioning
confidence: 97%
“…These data suggest the participation of major technologically important contaminants (most likely, O, C) forming complexes with native defects created by irradiation. At the same time, in AlGaN/GaN, AlN/GaN with semi-insulating GaN(Fe) buffers grown by MBE [181,182,264] the centers dominant in reverse DLTS were the 0.25 and 0.6 eV prevalent in the GaN buffer.…”
Section: Algan/gan Heterojunctions: the Origin Of Two-dimensional Gasmentioning
confidence: 98%
See 1 more Smart Citation
“…The Fermi level pinning approximately 0.5-0.6 eV below the conduction band minimum ͑CBM͒ has also been confirmed using a capacitancevoltage method. 15 Since the charge state of Fe Ga 3+/2+ level is transferred from Fe Ga 3+ to Fe Ga 2+ by capturing an electron, an Fe atom acts as a compensating deep acceptor in GaN. As the Fe concentration, ͓Fe͔, is increased sufficiently in moderately n-type GaN, the Fermi level shifts toward the midgap and Fe Ga 3+/2+ level is inversely transferred from Fe Ga 2+ to Fe Ga 3+ by releasing an electron.…”
Section: Thermal Stability Of Semi-insulating Property Of Fe-doped Gamentioning
confidence: 99%
“…The 50% degradation of the 2DEG conductivity happens at several times higher doses ͑close to 3 ϫ 10 16 cm −2 versus 6.5ϫ 10 15 High electron mobility transistor ͑HEMT͒ structures based on AlGaN / GaN and AlN / GaN are of interest for high-power microwave applications. The irradiation increases the resistivity of the GaN buffer due to compensation by radiation defects with levels near E c − 1 eV and decreases the mobility of the two-dimensional electron gas ͑2DEG͒ near the AlGaN / GaN ͑or AlN / GaN͒ interface.…”
mentioning
confidence: 99%